2011
DOI: 10.1103/physrevb.84.054536
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle energy relaxation times in NbN/CuNi nanostripes from critical velocity measurements

Abstract: The dynamic instability of the moving vortex lattice at high driving currents in NbN/CuNi-based and NbN nanostripes designed for optical detection has been studied. By applying the model proposed by Larkin and Ovchinnikov [Zh. Eksp. Teor. Fiz. 68, 1915 (1975)], from the critical velocity v ∗ for the occurrence of the instability, it was possible to estimate the values of the quasiparticle relaxation times τE. The results show that the NbN/CuNi-based devices are characterized by shorter values of τE compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 45 publications
(78 reference statements)
6
23
1
Order By: Relevance
“…When the bias current is further increased, the linear flux-flow regime is present until a certain value I * , where a sudden jump of the voltage V * takes place in agreement with the Larkin-Ovchinnikov theory [9]. Such instabilities were previously observed in a number of different superconducting systems [1,6,7,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. V * is related to the so-called critical velocity v * by the relation [9] At high fields the jump is replaced by a more continuous transition towards the normal state, as is clearly seen looking at the curves corresponding to the fields of 0.4 and 0.5 T in the inset of Fig.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…When the bias current is further increased, the linear flux-flow regime is present until a certain value I * , where a sudden jump of the voltage V * takes place in agreement with the Larkin-Ovchinnikov theory [9]. Such instabilities were previously observed in a number of different superconducting systems [1,6,7,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. V * is related to the so-called critical velocity v * by the relation [9] At high fields the jump is replaced by a more continuous transition towards the normal state, as is clearly seen looking at the curves corresponding to the fields of 0.4 and 0.5 T in the inset of Fig.…”
Section: Resultssupporting
confidence: 54%
“…In contrast, in the case of S/F hybrids a thin F layer will be completely proximized so that different superconducting properties appear at a distance of the order of α. Moreover, by studying the dynamic properties of the vortex lattice in S/F structures, it was found that the performance of the detecting devices in terms of the quasiparticle relaxation rates seems to be strongly enhanced by the presence of the F layer [1,2,[6][7][8]. In particular, from the analysis of the critical velocity v * for the occurrence of the instability of the moving vortex lattice [9], information on the quasiparticle relaxation time τ E was obtained, and it was shown that in order to reduce the values of τ E it is useful to couple the superconductor to a strong ferromagnet, such as permalloy [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we propose that single-photon response can occur also in a superconducting strip in which vortices are present induced by a perpendicular magnetic field. In such films, an applied current induces a resistive flux flow state, which transits into a more resistive state at a "quench" current I q (H ) > I c (H ) [5][6][7][8][9][10][11][12][13][14][15][16]. The critical current I c (H ) is magnetic field dependent, because it controls the density of vortices.…”
Section: Introductionmentioning
confidence: 99%
“…Within this idea, we have investigated the phenomenon of dark counts in nanostripes based on high-T C superconducting YBa 2 Cu 3 O 7-x (YBCO) and superconductor/ferromagnet NbN/NiCu and YBa 2 Cu 3 O 7-x /L 0.7 Sr 0.3 MnO 3 (YBCO/LSMO) hybrids. In the case of hybrid structures, our previous studies have shown that the presence of an ultrathin ferromagnetic overlayer influences the superconducting properties of the bilayer, in terms of the critical current density J C , T C , as well as the electron relaxation time [13][14][15][16]. In work presented here, we focus on dark-count measurements in hybrid, superconductor/ferromagnet (S/F) stripes patterned from nanobilayers consisting of ultrathin NiCu weak ferromagnetic films deposited top of ultrathin NbN films, as well as from pure NbN films fabricated in the same conditions and treated as a reference.…”
Section: Investigation Of Dark Counts In Innovative Materials For Supmentioning
confidence: 99%